Metallointercalators synthesis and techniques to probe their interactions with biomolecules - Aldrich-Wright, Janice (Springer, 2011)
A comprehensive treatment of the characterisation techniques used in investigating inorganic and organic molecules that interact with biomolecules is presented to the reader in a clear fashion. The work consists of two parts: (i) synthetic aspects of metallointercalators along with targeting and improving transport and (ii) the various techniques that are used for probing their interactions, such as; DNA-NMR, PGSE-NMR, DNA ESI-MS, Linear and Circular Dichroism, Fluorescence Spectroscopy, Confocal Microscopy, Viscosity, TGA and dialysis, Microarrays, biological analysis. Chapters are devoted to the synthesis and the techniques used to study the interactions of inorganic complexes with biomolecules. Considerably detailed examples are used to help illustrate the application of these techniques. This book is a useful resource for an array of inorganic and organic advanced undergraduate and graduate courses and for researchers in drug discovery.